Brand society : how brands transform management and lifestyle - Kornberger, Martin, 1974- (Cambridge : Cambridge University Press, 2010)
Brands are a fait accompli: they represent a mountain range of evidence in search of a theory. They are much exploited, but little explored. In this book, Martin Kornberger sets out to rectify the ratio between exploiting and exploring through sketching out a theory of the Brand Society. Most attempts to explain the role of brands focus on brands either as marketing and management tools (business perspective) or a symptoms of consumerism (sociological perspective). Brand Society combines these perspectives to show how brands have the power to transform both the organizations that develop them and the lifestyles of the individuals who consume them. This holistic approach shows how brands function as a medium between producers and consumers in a way that is rapidly transforming our economy and society. That's the bottom line of the Brand Society: brands are a new way of organizing production and managing consumption. Using an array of practical case studies from a diverse set of organizations, this book provides a fascinating account of the way in which brands influence the lives of individuals and the organizations they work in.
Brands and branding -- Introduction: The brand society -- Making sense of brands -- The making of brands -- How brands transform management -- Identity -- Culture -- Innovation -- How brands transform lifestyle -- Politics -- Ethics -- Aesthetics.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: elektronické knihy; electronic books; Brand name products; Brand name products -- Management; Popular culture